Multifaceted Immunomodulatory Effects of the BTK Inhibitors Ibrutinib and Acalabrutinib on Different Immune Cell Subsets – Beyond B Lymphocytes - Zhu, Sining; Gokhale, Samantha; Jung, Jaeyong; Spirollari, Eris; Tsai, Jemmie; Arceo, Johann; Wu, Ben Wang; Victor, Eton; Xie, Ping (Frontiers in Cell and Developmental Biology, 2021)
The clinical success of the two BTK inhibitors, ibrutinib and acalabrutinib, represents a major breakthrough in the treatment of chronic lymphocytic leukemia (CLL) and has also revolutionized the treatment options for other B cell malignancies. Increasing evidence indicates that in addition to their direct effects on B lymphocytes, both BTK inhibitors also directly impact the homeostasis, phenotype and function of many other cell subsets of the immune system, which contribute to their high efficacy as well as adverse effects observed in CLL patients. In this review, we attempt to provide an overview on the overlapping and differential effects of ibrutinib and acalabrutinib on specific receptor signaling pathways in different immune cell subsets other than B cells, including T cells, NK cells, monocytes, macrophages, granulocytes, myeloid-derived suppressor cells, dendritic cells, osteoclasts, mast cells and platelets. The shared and distinct effects of ibrutinib versus acalabrutinib are mediated through BTK-dependent and BTK-independent mechanisms, respectively. Such immunomodulatory effects of the two drugs have fueled myriad explorations of their repurposing opportunities for the treatment of a wide variety of other human diseases involving immune dysregulation.